A Rare Variation of Inferior Laryngeal Nerve: Nonrecurrent Laryngeal Nerve - BİNNETOĞLU, ADEM; YUMUŞAKHUYLU, ALİ CEMAL (GALENOS YAYINCILIK, 2015)
A nonrecurrent laryngeal nerve variant of the inferior laryngeal nerve is very rarely seen, and surgeons should keep it in mind during thyroid surgery. Preoperative findings, like situs invertus and dysphagia lusoria, may be suggestive of a nonrecurrent laryngeal nerve. However, these findings always have not to be together with nonrecurrent laryngeal nerve, like our case.
Keywords: Thyroid surgery; nonrecurrent laryngeal nerve; dysphagia lusoria